Diastereoselective intramolecular hydride transfer - Gandamana, Dhika Aditya (Nanyang Technological University, 2021)
This thesis focuses on the synthetic applications of diastereoselective 1,5-hydride transfer to undergo reduction of transient carbocation, which is generated upon electrophilic activation of alkenes or alcohols. Diastereoselective assembly of these stereogenic centers is enabled via the 6-membered chair-like transition state.